Deletion of P2Y(2) receptor reveals a role for lymphotoxin-α in fatty streak formation() - Qian, Shaomin (Vascul Pharmacol, 2016)
BACKGROUND: Lymphotoxin alpha (LTα) is expressed in human atherosclerotic lesions and genetic variations in the LTα pathway have been linked to myocardial infarction. Activation of the P2Y(2) nucleotide receptor (P2Y(2)R) regulates the production of LTα. in vitro. We aimed to uncover a potential pathway linking purinergic receptor to LTα-mediated inflammatory processes pivotal to the early stages of atherosclerosis in apolipoprotein E (ApoE(−/−)) deficient mice. METHODS AND RESULTS: En face immunostaining revealed that P2Y(2)R and VCAM-1 are preferentially expressed in the atherosclerosis prone site of the mouse aortic sinus. Deletion of the P2Y(2)R gene suppresses VCAM-1 expression. Compared with ApoE(−/−)mice, ApoE(−/−)mice lacking the P2Y(2)R gene (ApoE(−/−)/P2Y(2)R(−/−)) did not develop fatty streak lesions when fed a standard chow diet for 15 weeks. Systemic and CD4(+) T cell production of the pro-inflammatory cytokine lymphotoxin-alpha (LTα) were specifically inhibited in ApoE(−/−)/P2Y(2)R(−/−) mice. Anti-LTα preventive treatment was initiated in ApoE(−/−) mice with intraperitoneal administration of recombinant human tumor necrosis factor receptor 1 fusion protein (TNFR1-Fc) on 5 consecutive days before the disease onset. Remarkably, none of the TNFR1:Fc-treated ApoE(−/−) mice exhibited atherosclerotic lesions at any developmental stage. SIGNIFICANCE: ApoE(−/−) mice deficient in P2Y(2)R exhibit low endothelial cell VCAM-1 levels, decreased production of LTα and delayed onset of atherosclerosis. These data suggest that targeting this nucleotide receptor could be an effective therapeutic approach in atherosclerosis.